Cyclic Polypeptide D7 Protects Bone Marrow Mesenchymal Cells and Promotes Chondrogenesis during Osteonecrosis of the Femoral Head via Growth Differentiation Factor 15-Mediated Redox Signaling. (3rd March 2022) - Chen, Jiazheng; Cui, Zichen; Wang, Yi; Lyu, Linmao; Feng, Changgong; Feng, Dianjie; Cheng, Yifan; Li, Ziqing; Sun, Shui
Abstract : Osteonecrosis of the femoral head (ONFH) is a debilitating disease that is closely associated with the clinical application of high-dose glucocorticoids. Elevated oxidative stress contributes to the pathophysiological changes observed in ONFH. The lack of effective treatments besides surgical intervention highlights the importance of finding novel therapeutics. Our previous studies demonstrated that D7, a cyclic polypeptide, enhances the adhesion, expansion, and proliferation of bone marrow mesenchymal stem cells (BMSCs). Therefore, in this study, we investigated the therapeutic effects of D7 against ONFH in BMSCs and evaluated the underlying mechanisms. First, we screened for ONFH risk factors. Then, we applied D7 treatment to steroid-induced ONFH (SONFH) in an in vitro model produced by dexamethasone (DEX) to further elucidate the underlying mechanisms. We found negative correlations among oxidative stress marker expression, growth differentiation factor 15 (GDF15) levels, and ONFH. Furthermore, we demonstrated that DEX inhibited the proliferation and induced apoptosis of BMSCs by suppressing GDF15/AKT/mammalian target of rapamycin (mTOR) signaling. D7 alleviated DEX-induced BMSCs injury and restored the chondrogenic function of BMSCs by activating GDF15/AKT/mTOR signaling. In addition, DEX-induced excessive reactive oxygen species (ROS) generation was an upstream trigger of GDF15-mediated signaling, and D7 ameliorated this DEX-induced redox imbalance by restoring the expression of antioxidants, including superoxide dismutase (SOD) 1, SOD2, and catalase, via regulation of GDF15 expression. In conclusion, our findings revealed the potential therapeutic effects of D7 in SONFH and showed that this protective function may be mediated via inhibition of DEX-induced ROS and activation of GDF15/AKT/mTOR signaling, thereby providing insights into the potential applications of D7 in SONFH treatment.